Անիի պատմութեան շադադեան շրջանի մի դրուագի մասին - Պօղոսեան, Աշխունջ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Вскоре после завоевания столицы Багратидов – города Ани, сельджукский султан Алп Арслан продал его курдскому эмиру Гандзака Фадлуну. Историк XIII века Вардан Аревелци по этому поводу сообщает, что взамен Фадлун дал султану узорчатую «златокованную картину» (ոսկիակուռ նկարս ծաղկոցի). Мнения исследователей расходятся в толковании смысла этих слов. Некоторые думают, что речь идет об иконах, другие отрицают возможность такого рода торга. Анализируя сведения, касающиеся различных тканей в эпоху Арабского халифата, автор заключает, что в словах «златокованная картина» Вардана Аревелци имел в виду роскошные златотканые ткани, одним из центров производства которой был город Двин. Shortly after capturing Ani, the Armenian Bagratid capital, Seljuk Sultan Alp Arslan sold the city to Patlun, Kurdish Emir of Gandzak. The historian Vardan Areveltsi wrote that Patlun “took Ani from Alp Arslan giving him a “gold-plated flower painting”. Researchers disagree on the meaning of “gold-plated flower painting” (ոսկիակուռ նկարս ծաղկոցի). Some of them think that this refers to icons, others simply rule out the presence of fabrics in this deal. Analyzing the information on various fabrics produced in the era of the Arab Caliphate, the author concludes that in fact, by saying “gold-plated flower painting”, the historian meant luxurious gold-woven royal fabrics, one of the production centers of which was Dvin.
Keywords: History